The Impact of Copper on the Mechanical Properties of Cast Motorcycle Cylinder Blocks - Salman, .; Sinarep, .; Paryanto Dwi, Setyawan; Hendry Sakke, Tira; Muhammad Nur, Mahadika (INTI International University, 2024)
Enhancing the mechanical properties of cast products can be achieved by adding other elements. This research investigates the effect of copper (Cu) on the mechanical properties of cast motorcycle cylinder blocks, verified through microstructure analysis.Experiments were conducted by adding varying amounts of copper (Cu) at 5%, 10%, and 15%, with a casting temperature of 1010°C using a metal mold. Data collection included hardness testing, tensile strength testing, and microstructure analysis.The results showed that increasing the percentage of copper (Cu) in the cylinder block casting led to significant improvements in mechanical properties. The highest Vickers hardness was achieved with the addition of 15% Cu, measuring 229.23 HV. Similarly, the highest tensile strength was observed with the 15% Cu addition, reaching 104.218 MPa. Microstructure analysis revealed that the casting results predominantly consisted of α Al+θ (CuAl₂)+βSi phases, which were smaller compared to the α Al phase